1987
DOI: 10.1111/j.1365-3059.1987.tb02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crown rust on regrowth, competitive ability and nutritional quality of perennial and Italian ryegrasses

Abstract: Infection of susceptible cultivars of perennial (Lolium perenne) and Italian (Lolium multifiorum) ryegrasses with crown rust {Puccinia coronata) reduced yield measured 6 weeks after infection and at two regrowth cuts. In perennial, but not Italian, ryegrass, rust infection of mixed swards of a resistant and a susceptible cultivar reduced the contribution to yield made by the susceptible cultivar and increased that of the resistant cultivar. This effect persisted for three regrowth cuts. The trend in effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
5

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 7 publications
1
36
2
5
Order By: Relevance
“…Grasslands Ruanui have been recorded (Lancashire & Latch 1966, 1970, leading to clover dominance in mixed ryegrass/clover swards, and reductions in root weight, tiller number, and leaf area have been directly related to disease severity (Lancashire & Latch 1966;Plummer et al 1990). These results mirror similar findings from the United Kingdom, where infection has also been shown to alter the chemical composition of affected plants (Potter 1987).…”
Section: Fungal Pathogenssupporting
confidence: 70%
“…Grasslands Ruanui have been recorded (Lancashire & Latch 1966, 1970, leading to clover dominance in mixed ryegrass/clover swards, and reductions in root weight, tiller number, and leaf area have been directly related to disease severity (Lancashire & Latch 1966;Plummer et al 1990). These results mirror similar findings from the United Kingdom, where infection has also been shown to alter the chemical composition of affected plants (Potter 1987).…”
Section: Fungal Pathogenssupporting
confidence: 70%
“…In addition, overseas research has shown crown rust can reduce the nutritional value (e.g. water-soluble carbohydrates (WSC)) of the herbage (Potter 1987;Smit et al 2005). When Armstrong & Rumball (1976) screened 48 overseas cultivars they found no consistent patterns between rust susceptibility and geographic or climatic origins of cultivars, with age of the cultivar being the best predictor of susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…In species grown for their vegetative organs, such as L. perenne, foliar diseases are especially important as they are often correlated with reductions in yield and quality. This is the case for crown rust infections caused by the biotrophic fungus Puccinia coronata (Potter, 1987;Plummer et al, 1990). The severity of crown rust infections can be reduced by good management practices, such as the use of resistant cultivars (Van Bockstaele and Baert, 2004).…”
Section: Introductionmentioning
confidence: 99%